2017
DOI: 10.1136/oemed-2016-103980
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal NO2exposure and ultrasound measures of foetal growth: a prospective cohort study in Wuhan, China

Abstract: In this prospective study of Chinese women, maternal NO exposure was inversely associated with foetal growth, and the association was stronger among female babies and smoking mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Common among these studies are assessments that examine exposures averaged across multiple weeks, months, or trimesters. Wang et al 16 reported associations between NO 2 exposure aggregated across the first 22 weeks of pregnancy with changes in BPD, AC, and FL from the second and third trimesters. A study of Korean women 15 also revealed reductions in fetal head size and length between the second and third trimesters associated with aggregated NO 2 exposure across the entire pregnancy period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common among these studies are assessments that examine exposures averaged across multiple weeks, months, or trimesters. Wang et al 16 reported associations between NO 2 exposure aggregated across the first 22 weeks of pregnancy with changes in BPD, AC, and FL from the second and third trimesters. A study of Korean women 15 also revealed reductions in fetal head size and length between the second and third trimesters associated with aggregated NO 2 exposure across the entire pregnancy period.…”
Section: Discussionmentioning
confidence: 99%
“…2 Moreover, all studies included in that review assessed exposure aggregated by trimester or by periods approximating trimesters (e.g., early, mid-, and late-pregnancy). Although six additional studies [11][12][13][14][15][16] have been published since July 2017 (the date before which studies included in the Fu et al 2 review was published), only three to our knowledge have since examined NO 2 exposure. [14][15][16] While these three studies each provide further evidence of associations between NO 2 exposures and altered fetal growth, they have also relied on relatively large exposure windows (e.g., trimesters) hindering their ability to evaluate sensitive windows of exposure.…”
mentioning
confidence: 99%
“…An observational study in Spain found that nitrogen dioxide (NO 2 ) exposure during pregnancy was associated with decreased biparietal diameter, abdominal circumference, and estimated fetal weight [ 28 30 ]. NO 2 also has been associated with significant inverse effects on fetal growth in observational cohorts in Los Angeles, California [ 31 ], China [ 32 ], and the Netherlands [ 33 ]. Additionally, studies have shown PM with an aerodynamic diameter of 10 m or less (PM 10 ) [ 31 , 33 37 ] and PM 2.5 [ 34 , 38 40 ] have adverse effects on fetal growth.…”
Section: Introductionmentioning
confidence: 99%